PENGEMBANGAN MODEL PEMBELAJARAN CIVIC REPORTING DALAM MATA KULIAH PENDIDIKAN KEWARGANEGARAAN UNTUK MENINGKATKAN CIVIC RESPONSIBILITY DAN CIVIC ENGAGEMENT MAHASISWA - Ita Aristia Sa’ida; SahrI, Sahri (Journal of Innovation Research and Knowledge, 2024)
The development of democratic citizens in the 21st century requires mastery of civic competencies, including civic responsibility and civic engagement. This study aims to develop a civic reporting-based learning model as a method to increase student civic responsibility and engagement. The research was conducted using a classroom action research method with the Bachman cycle. Participants were second-semester students of the Civic Education course at a private university in East Java. Data were collected through observation, interviews, documentation, and reflective notes. The results indicate an improvement in students’ ability to identify, communicate, and respond to civic issues in their communities. The civic reporting model also enhanced students’ empathy and responsibility through authentic involvement in real-world issues. This paper provides a detailed explanation of the planning, implementation, and evaluation phases and offers a replicable model for character-based civic education